THE EFFECT OF INTERNALIZATION OF LOCAL CULTURE ON AUDITOR'S SKEPTICISM - Monika Handojono; Theofilus J F K Matrutty (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
For several hundred years tribes in the Maluku of Eastern Indonesia have followed the cultural practice of pela-gandong. Pela-Gandong is a form of brotherhood between two or more villages, with its foundation being in blood relationships. Socially, pela-gandong is acknowledged as beneficial in spreading peace and harmony among differing ethnic groups. However, the practice raises questions of its influence on specific professional roles such as auditing. Using Self-Determination Theory, this study examines the impact of pela-gandong on an auditor’s personal values, particularly the need for impartial auditor skepticism. By collecting data from 69 auditors across three local government municipalities and one city in Maluku, the findings suggest that the personal value (openness to change) and internalization of Pela–Gandong decreases auditor skepticism. The study recommends the need to further develop an approach that will increase auditors’ awareness of cultural issues.